Access audit & scoring compliance assessment for the elderly-friendly mosque. Case study: heritage mosque - Masjid Diraja Sultan Suleiman & National Mosque Of Malaysia - Che Wil@Ismail, Che Muhamad Hanif; Ismail, Hafiszah (Universiti Teknologi MARA, Kedah, 2023)
The tremendous growth in the senior population makes Malaysia's ageing phenomenon inevitable. Additionally, Malaysia is seeing a tremendous rise in the urban population. It is becoming more and more important to examine how urbanisation affects the elderly because of how quickly it is occurring and how it affects the population. To effectively prepare nations for the opportunities and problems that an ageing population will present, a detailed assessment of their requirements is necessary. For the current policy and related elderly care provision framework to be changed, it is essential to comprehend the primary concerns surrounding the needs of the Malaysian elderly community. Thus, this study aims to produce an access audit by scoring for elderly- friendly heritage building focusing on mosque with reference to Malaysian Standards and related Acts/By-Laws. This study uses methodology (i) interview to validate draft access audit from literature and (ii) observation on scoring of access audit was used to obtain the data. Access audit is an examination of an existing building, its facilities and services, against pre-determine criteria to access its usability. The selected heritage building for this study is Masjid DiRaja Sultan Suleiman and National Mosque of Malaysia. In conclusion, this research to study the access audit by scoring for the elderly- friendly heritage building (mosque) to provided comfortably and safe to elderly.